2007
DOI: 10.1111/j.1365-2249.2007.03560.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent of respiratory syncytial virus in human dendritic cells and influence of nitric oxide

Abstract: SummaryThe annual epidemics of respiratory syncytial virus (RSV) infection are probably explained by poor herd immunity and the existence of a dormant reservoir of virus that is activated by an unknown trigger. The virus causes particular problems in infants, the elderly and patients with chronic obstructive airways disease (COPD). During two consecutive winters, human monocyte-derived dendritic cells (DCs) were exposed on a single occasion to one of two forms of RSV labelled with a fluorescent expresser genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 43 publications
0
40
1
3
Order By: Relevance
“…Furthermore, when the HEp-2 parent cell line was treated with increasing concentrations of the chemical NO donor, Snitroso-N-acetyl-penicillamine (SNAP), no inhibition of viral replication was observed except at high concentration of SNAP, suggesting that the NO derived from endogenous iNOS expression was much more efficient at inhibiting RSV replication than was the addition of the exogenous NO via the chemical donor SNAP (9). In a model of persistently infected dendritic cells, endogenous NO production seemed to be important in controlling RSV replication, as shown by increased viral titers in cells treated with the NOS inhibitor nitro-l-arginine methyl ester (L-NAME) (103).…”
Section: A No Production and Inos Expression In Rsv Infectionmentioning
confidence: 99%
“…Furthermore, when the HEp-2 parent cell line was treated with increasing concentrations of the chemical NO donor, Snitroso-N-acetyl-penicillamine (SNAP), no inhibition of viral replication was observed except at high concentration of SNAP, suggesting that the NO derived from endogenous iNOS expression was much more efficient at inhibiting RSV replication than was the addition of the exogenous NO via the chemical donor SNAP (9). In a model of persistently infected dendritic cells, endogenous NO production seemed to be important in controlling RSV replication, as shown by increased viral titers in cells treated with the NOS inhibitor nitro-l-arginine methyl ester (L-NAME) (103).…”
Section: A No Production and Inos Expression In Rsv Infectionmentioning
confidence: 99%
“…Such a defect would slow virus spread and reduce the cytopathic effects of cell-cell fusion, such that the virus itself would be noncytopathic. Persistent RSV infections have also been described in mice, in patients with chronic obstructive pulmonary disease, and in human dendritic cells maintained ex vivo (12,23,26,48,57).…”
Section: Discussionmentioning
confidence: 99%
“…6 Subsequently, we have shown that the virus is able to lie latent in a population of dendritic cells for many months and that replication can be triggered by exogenous nitric oxide ͓NO͔ or an iNOS inhibitor. 7 We have also found evidence of RSV antigen in the monocyte fraction of cells obtained from specimens of lung resected from adults during the summer months, 8 suggesting that pulmonary dendritic cells may be the reservoir during the viruses 'summer holidays. ' These observations would explain why RSV might be found in sputum samples obtained from COPD patients outside the epidemic period-tobacco smoke contains significant quantities of nitric oxide and this may contribute to chronic or recurrent replication of the virus which in turn may contribute to inflammation and enhanced rate of decline in lung function.…”
mentioning
confidence: 95%
“…Although we agree that animal models have certain limitations such as the need to use high viral titers to reproduce the disease, we and others have demonstrated that the pathology induced by RSV is not negligible, 5,6 in fact, it is directly associated with the degree of inoculum attenuation and/or inactivation. 7 The nature of the host immune response to RSV is not well understood, and the published data of the T H 1-T H 2 cytokine responses in both humans and animal models is contradictory probably because of differences in study designs. [7][8][9][10][11] A careful selection of a population-based cohort is critical to define the contribution of the T H 1/T H 2 immune response in RSV disease and well defined studies are needed.…”
mentioning
confidence: 98%
See 1 more Smart Citation